INCREASING ALUMINIUM CONTENT OF ALUMINOSILICATE CRYSTALS SYNTHESIZED FROM THE BIOSILICA CYCLOTELLA STRIATA TBI STRAIN - Syahra Almunadya, Novi
In previous studies, aluminosilicates had been synthesized from biosilica Cyclotella striata TBI strain. The aluminosilicate had also been used as a catalyst for the synthesis of tertiary ethyl butyl ether (ETBE) obtained from ethanol and tertiary butyl alcohol. However, the catalytic power of aluminosilicate was still very low due to the low aluminum content in aluminosilicate. The purpose of this study is to find the condition of aluminosilicate synthesis from biosilica C. striata TBI strain with high aluminum content and test its catalytic power. This research was done in following steps: cultivation of diatom C. striata TBI strain, isolation biosilica from C. striata TBI strains, modification the biosilica C. striata TBI strain into aluminosilicate with high levels of aluminum in aluminosilicate, activation aluminosilicate into acid catalysts, and examination of catalytic activity in synthesis of ETBE. The results showed that the biomass productivity of C. striata TBI strain cultivated with an initial cell density of 500,000 cells/mL in a volume of 1500 L ranged from 0.274 to 0.407 g day–1 L–1. Si and O content of isolated biosilica C. striata TBI strain which the total amount is 100% was confirmed by XRF and EDS. Si-O-Si vibration band of biosilica was observed at wave numbers 450, 795, and 1105 cm–1 by FTIR spectra. O-Al-O vibrations were observed at wave number 554 cm-1 and Si-O-Al vibrations at wave number 1242 cm-1 indicate that modification of biosilica into aluminosilicate was successfully done. Five variations of aluminosilicates with Al/Si mole ratio of 1,4, 2,7, 3,3, 8,3 and 54% resembled to ZSM-5 crystals. The activated aluminosilicate with Al/Si mole ratio of 54% was analyzed using GC-MS to examine its catalytic power in ETBE synthesis. The ETBE products was confirmed on retention time at 2.11.